Fecal Microbiota Transplantation Donor and Dietary Fiber Intervention Collectively Contribute to Gut Health in a Mouse Model - Zhong, Yifan; Cao, Jiahong; Ma, Yanfei; Zhang, Yu; Liu, Jianxin; Wang, Haifeng (Frontiers in Immunology, 2022)
Transforming the gut microbiota has turned into the most intriguing target for interventions in multiple gastrointestinal and non-gastrointestinal disorders. Fecal microbial transplantation (FMT) is a therapeutic tool that administrating feces collected from heathy donors into patients to help replenish gut microbial balance. Considering the random donor selection, to maintain the optimal microbiota eco system post FMT is critical for therapy outcomes but challenging. Aiming to study the interventions of different diets on recipients’ gut microbiota post FMT originated from donors with different diets, we performed FMT from domestic vs. wild pigs that are living with low-fiber vs. high-fiber diets into pseudo-GF mouse, followed with fiber-free (FF) or fiber-rich (FR) diets post FMT. Different patterns of gut microbiota and metabolites were observed when mice FMT from different donors paired with different dietary fiber content. Enrichment of bacteria, including Akkermansia and Parabacteriodes, together with alteration of metabolites, including palmitic acid, stearic acid, and nicotinic acid, were noted to improve crypt length and mucus layer in the gut in mice FMT from wild pigs fed a FR diet. The results provide novel insight into the different responses of reconstructed gut microbiota by FMT to dietary fiber. Our study highlighted the importance of post FMT precise dietary interventions.